Strengthening the Indonesia National Water and Sanitation Information Services Center for Improved Planning - World Bank (Washington, DC, 2015)
This report summarizes the main achievements of technical assistance provided under the Water Supply and Sanitation Policy Formulation and Action Planning Facility to the Indonesian National Water and Sanitation Information Services (NAWASIS) Centre from October 2012 to December 2014 to further consolidate the water supply and sanitation (WSS) data and information management instrument (NAWASIS Info) as a modular part of the overall services provided by the Centre. It highlights some of the continued challenges of effective WSS monitoring, and proposes strategies for further WSS data and information management development. This reports is divided into nine sections. The first three sections provide background information, including the report purpose, general context and description of the assistance. Sections four to seven describe the progress made in achieving the expected outcomes, while the final two sections describe the future of NAWASIS and some recommendations on moving forward.